Effect of time parameters of pulsed bias potential on intrinsic stress in TiN coating deposited from inclined ion beam - Kalinichenko, A.I.; Perepelkin, S.S.; Reshetnyak, E.N.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2018)
In the model of the nonlocal thermoelastic peak of low-energy ion, the formation of intrinsic stress in the coating deposited from inclined ion beam at the pulsed bias potential with different values of pulse frequency f and duration tₚ is analyzed. The stress in the TiN coating deposited from Ti ion flux in the mode of the pulsed bias potential at various angles of incidence α and different values of time parameter τ = f tₚ is calculated. It is established that in the region 0.01 < τ < 0.2 the stress σ varies nonmonotonically with increasing α, decreasing up to angles of incidence α ~ 70º with subsequent growth. The calculated curve σ(τ) coincides with the experimental data at U = 1.5 kV and α = 0. У моделі нелокального термопружного піку низькоенергетичного іона проаналізовано формування внутрішніх напружень в покритті, що осаджується з похилого пучка іонів при імпульсному потенціалі зміщення з різними значеннями частоти f і тривалості tₚ імпульсів. Проведено розрахунок напружень в TiN-покритті, що осідає з потоку іонів Ti в режимі імпульсного потенціалу при різних кутах падіння іонів α і різних значеннях часового параметра τ = f tₚ. Установлено, що в області 0,01 < τ < 0,2 при збільшенні α напруга σ змінюється немонотонно, зменшуючись аж до кутів падіння α ~ 70º з наступним ростом, причому при U = 1,5 кВ і α = 0 хід розрахункової кривої σ(τ) збігається з експериментальними даними. В модели нелокального термоупругого пика низкоэнергетического иона проанализировано формирование внутренних напряжений в покрытии, осаждаемом из наклонного пучка ионов при импульсном потенциале смещения с различными значениями частоты f и длительности tₚ импульсов. Проведен расчет напряжений σ в TiN-покрытии, осаждаемом из потока ионов Ti в режиме импульсного потенциала при различных углах падения ионов α и различных значениях временного параметра τ = f tₚ. Установлено, что в области 0,01 < τ <0,2 при увеличении α напряжение σ изменяется немонотонно, уменьшаясь вплоть до углов падения α ~ 70º с последующим ростом, причем при U = 1,5 кВ и α = 0 ход расчетной кривой σ(τ) совпадает с экспериментальными данными.